A COMPARATIVE EFFICACY OF METHANOLIC EXTRACTS OF AZADIRACHTA INDICA AND CASSIA FISTULA AGAINST TERMITES (The Research of Medical Science Review, 2025)
Termites are insects consisting of 3000 species, of which 300 are considered pests. They feed on the decomposition of organic wastes like leaves, animal dung, and living or dead wood, causing significant economic damage. Fast-acting termiticides are frequently used to control termites. However, this practice has significant biological and environmental hazards. Medicinal plants have good insecticidal activity without any significant environmental risk. Therefore, the current study investigated the invitro toxic potential of Azadirachta indica and Cassia fistula against termites. Fresh leaves of Azadirachta indica and Cassia fistula were collected from their habitat in the Kohat district. Leaves were identified, rinsed, shade dried, and ground, and the crude methanolic extract was prepared. Termites were also collected from their natural habitat in the Kohat district. Termite species were identified, and a 24-hour invitro assay was conducted in triplicates using Petri dishes and various concentrations of both extracts of selected medicinal plants.Both selected medicinal plants revealed a notable dose-dependent anti-termite activity. In comparison, Azadirachta indica showed a maximum activity (20.86±4.16) at a concentration of 8 mg/ml, while a great activity was observed by Cassia fistula (26.84±4.61) at the same concentration. Permethrin was used as a positive control, which revealed (25.23±4.7) mortality at the same concentration. The current study concluded that the Azadirachta indica exhibits anti-termite potential. Cassia fistula might contain some anti-termite insecticidal compounds which need to be isolated and explored further to replace the hazardous chemical substances against termites.